A Digital Cognitive Aid for Anesthesia to Support Intraoperative Crisis Management: Results of the User-Centered Design Process - Schild, Stefanie; Sedlmayr, Brita; Schumacher, Ann-Kathrin; Sedlmayr, Martin; Prokosch, Hans-Ulrich; St. Pierre, Michael (JMIR mHealth and uHealth, 2019)
Background: Stressful situations during intraoperative emergencies have negative impact on human cognitive functions. Consequently, task performance may decrease and patient safety may be compromised. Cognitive aids can counteract these effects and support anesthesiologists in their crisis management. The Professional Association of German Anesthesiologists set up a project to develop a comprehensive set of digital cognitive aids for intraoperative emergencies. A parallel development for several software platforms and stationary and mobile devices will accommodate the inhomogeneity of the information technology infrastructure within German anesthesia departments.
CRIS-Team WoS Importer:2019-05-24